The longitudinal role of early family risks and early social-emotional problems for friendship quality in preadolescence-A regression model. - Olivia Gasser-Haas (Public Library of Science (PLoS), 2021)
The quality of a best friendship provides information about how developmentally beneficial it is. However, little is known about possible early risk factors that influence later friendship quality. The present study examined the role of family risks and social-emotional problems (behavioral problems, peer problems, anxious, and depressive symptoms) in early childhood for positive (i.e., support and help) and negative (i.e., conflicts and betrayal) dimensions of friendship quality with their best friend in preadolescence. 293 children (47.9% female) aged 2-4, their parents and teachers participated in the study with three measurement occasions (T1; Mage = 2.81, T2; Mage = 3.76, T3; Mage = 9.69). The last measurement occasion was at the age of 9-11 years. Results of the longitudinal regression model showed that depressive symptoms in early childhood were associated with a lower positive dimension of friendship quality in preadolescence. In contrast, early anxious symptoms were related to a higher positive dimension of friendship quality six years later. Neither family risks, nor behavioral problems and peer problems in early childhood were linked to the positive dimension of friendship quality in preadolescence. No early predictors were found for the negative dimension of friendship quality. Possible reasons for the lack of associations are discussed. Findings suggest that children with early depressive symptoms at 3-5 years of age should be the targets of potential interventions to form high quality friendships in preadolescence. Possible interventions are mentioned.